Assessment of water quality using the Overall Index of Pollution and Comprehensive Pollution Index at the upper stretch of River Ganga: Pollution indices of River Ganga - Das, Basanta Kumar; Mishra, Sandeep Kumar; Kumar, Jeetendra; Alam, Absar; Jha, Dharm Nath; Shukla Das , Shyamal Chandra; Thakur, Venkatesh; Verma, Sushil Kumar; Singh, Upendra; Om Verma, Hari; Pandey, Amit Ranjan; Kumar, Vijay (Journal of the Inland Fisheries Society of India, 2023)
Overall Index of Pollution (OIP) and Comprehensive Pollution Index (CPI) are useful tools for assessing the consistency of surface water. A three-year (2017 to 2019) study was carried out using the OIP and CPI to assess the seasonal variation and pollution status of the upper stretch (Harshil, Tehri & Haridwar) of the River Ganga in India. Data obtained from the sample analysis showed that during all seasons, the OIP value of water quality was found to be excellent (OIP<1) in the upper stretch. However, the Comprehensive Pollution Index (CPI) value showed that River Ganga’s water quality falls in the category of slightly polluted (CPI = 0.41 to 1), except for Tehri above and below dam site, which falls in the sub-clean category (CPI 0.4) during the winter season. We may therefore infer that the upper stretch of the River Ganga’s water quality varies from excellent to slightly polluted based on the two indices (OIP & CPI)